Knowledge scores in annual and modular curriculum among medical students from Karachi, Pakistan - Saher Naseeb Uneeb; Saima Zainab; Aneeta Khoso; Abdul Basit (Journal of the Pakistan Medical Association, 2021)
Abstract Objective: To compare the knowledge scores of basic medical subjects among undergraduate medical students of annual versus modular system. Methods: A cross-sectional survey was conducted on 4th year undergraduate medical students of annual and modular system of Liaquat National Medical College, Pakistan. Study was conducted from 30th November 2017 to 1st June 2018 for a total of 6 months. Sample size was calculated to be 82 students. The data was collected using a structured questionnaire. The student’s t-test was applied to compare the mean difference of knowledge scores between the two groups. Results: Students in modular system retained better knowledge of anatomy as compared to annual students. While the annual system students retained higher knowledge in the subjects of community medicine and pharmacology. Mean knowledge score for annual was 12.98 (SD±2.92) and semester system students was 13.10 (SD±3.03). There was no significant difference observed in overall mean knowledge scores between the two groups (p-value = 0.85). Conclusion: Students in the annual system scored higher in pharmacology and community medicine. This highlights the need to address the issues of time allocation and implementation strategies for the subjects in the new system. There was no difference between overall knowledge scores in each group, hence it cannot be concluded that one system is superior to the other. Keywords: Knowledge retention, annual system, modular system, basic science, knowledge scores. Continuous...